Ideal Certification of Visual Arts in Nigeria through Valid Practical Assessment - Osariyekemwen, D.N.; Otimeyin, P.O.; Esebameh, G.O. (Universitas Pendidikan Indonesia, 2017)
ABSTRACT: The inappropriate practical assessment of the Visual Arts for ideal practical evaluation has necessitated the general outcry on the factors responsible for it. This paper tries to investigate the factors responsible for the non-compliance with credible practical assessment in Visual Arts for quality certification. It is giving some insight into solutions that will help in stamping out these inhibiting factors against the credible practical assessment in Visual Arts. When more emphasis are laid on practical courses and standard practical test examination conducted, it will go a long way in solving the unemployment problem observed as possible fallout of assessment methods and emphasis paper qualification at the expense of practical practice. It is suggested that examination materials be provided at least a month to the commencement of examination, more time should be allotted to practical examinations, supervision of practical examination should be handled with more seriousness, and the joint assessment of practical examination works be introduced. Finally, it is recommend possible ways of conducting practical examination to all stake holders in Visual Arts in Nigeria.KEY WORD: Practical Assessment; Visual Arts; Quality Certification; Examination Materials; National Development of Nigeria.Â ABSTRAKSI: â€œSertifikasi Ideal Seni Rupa di Nigeria melalui Penilaian Praktek yang Validâ€. Penilaian praktek Seni Rupa yang tidak tepat untuk evaluasi praktek yang ideal mengharuskan terjadinya kecaman umum terhadap faktor-faktor yang bertanggung jawab terhadapnya. Makalah ini mencoba untuk menyelidiki faktor-faktor yang bertanggung jawab atas ketidakpatuhan terhadap penilaian praktek yang kredibel dalam Seni Rupa untuk sertifikasi mutu. Ianya memberikan beberapa wawasan tentang solusi yang akan membantu dalam mencegah faktor penghambat terhadap penilaian praktek yang kredibel dalam Seni Rupa. Bila penekanan lebih diberikan pada kursus praktis dan ujian praktis standar yang dilakukan, ia akan sangat membantu dalam memecahkan masalah pengangguran yang diamati sebagai kemungkinan dampak metode penilaian dan penekanan pada kualifikasi kertas dengan mengorbankan ujian praktek. Disarankan agar bahan ujian diberikan paling sedikit sebulan sampai dengan dimulainya ujian, lebih banyak waktu yang harus diberikan untuk ujian praktek, pengawasan terhadap ujian praktek harus ditangani dengan lebih serius, dan penilaian bersama terhadap latihan ujian praktek diperkenalkan. Akhirnya, direkomendasikan berbagai cara melakukan ujian praktek untuk semua pemangku kepentingan Seni Rupa di Nigeria.KATA KUNCI: Penilaian Praktis; Seni Rupa; Sertifikasi Mutu; Bahan Ujian; Pembangunan Nasional Nigeria.Â Â About the Authors: D.N. Osariyekemwen, Ph.D. is a Lecturer at the Department of General Art and Industrial Design, Auchi Polytechnic, PMB 13, Auchi, Nigeria; P.O. Otimeyin, Ph.D. is a Lecturer at the Department of Ceramics, Auchi Polytechnic, PMB 13, Auchi, Nigeria; and G.O. Esebameh is a Lecturer at the Department of Graphics and Textiles, Auchi Polytechnic, PMB 13, Auchi, Nigeria. E-mails address of authors: osadanosa@gmail.com, otimeyinpius@yahoo.com, and continentalgeobameh@gmail.comHow to cite this article? Osariyekemwen, D.N., P.O. Otimeyin G.O. Esebameh. (2017). â€œIdeal Certification of Visual Arts in Nigeria through Valid Practical Assessmentâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.2(2), September, pp.155-162. Bandung, Indonesia: UPI [Indonesia University of Education] Press, ISSN 2527-3868 (print) and 2503-457X (online). Chronicle of the article: Accepted (April 6, 2017); Revised (June 13, 2017); and Published (September 30, 2017).